2007
DOI: 10.1007/s11144-007-5191-4
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemicals and catalytic properties of manganese-promoted vanadium phosphate (VPO) catalyst

Abstract: The addition of 1% Mn promoter to vanadium phosphate catalyst led to doubling of the specific surface area from 20.3 (unpromoted) to 39.4 m 2 g -1 . The XRD pattern of the Mn-promoted catalyst gave only the characteristics of the (VO) 2 P 2 O 7 phase, indicating that the Mn was incorporated into the crystal lattice of the catalyst. The Mn-promoted catalyst was also twice as active in removing the total amount of oxygen. However, since the only oxygen species related to V 4+ being removed and no oxygen species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…16 m 2 g -1 (for undoped), 14 m 2 g -1 for VPDBi1Fe1, 12 m 2 g -1 for VPDBi1Fe2 and 18 m 2 g -1 for VPDBi2Fe1. In our earlier studies, we had shown that the incorporation of 1% of Bi increased the surface area [3]; however, doping with 1% of Fe significantly lowered the surface area [6]. The higher concentration of Bi of doped catalyst (VPDBi2Fe1) in this study may encourage the formation of crystal phases with a slightly higher surface area and hence the slight variations in surface area we observe here are consistence with our earlier study.…”
Section: Catalysts Testingsupporting
confidence: 90%
See 2 more Smart Citations
“…16 m 2 g -1 (for undoped), 14 m 2 g -1 for VPDBi1Fe1, 12 m 2 g -1 for VPDBi1Fe2 and 18 m 2 g -1 for VPDBi2Fe1. In our earlier studies, we had shown that the incorporation of 1% of Bi increased the surface area [3]; however, doping with 1% of Fe significantly lowered the surface area [6]. The higher concentration of Bi of doped catalyst (VPDBi2Fe1) in this study may encourage the formation of crystal phases with a slightly higher surface area and hence the slight variations in surface area we observe here are consistence with our earlier study.…”
Section: Catalysts Testingsupporting
confidence: 90%
“…catalyst are necessary [15][16][17] although an excess of this oxygen was observed to be detrimental. Our previous result on Bi-promoted VPD catalysts shows an enhancement of the activity [3] whereas Fe was found to reduce the conversion of the catalyst which was prepared via dihydrate route [6]. A mixture of Bi-Fe dopants in this case induced to a low activity of the catalyst due to two salient observations.…”
Section: Temperature Programmed Reduction (Tpr) In H 2 /Armentioning
confidence: 70%
See 1 more Smart Citation
“…The promotional effects of cobalt (148,150,165,167,169,173,179,182,(191)(192)(193)(194)(195)(196)(197)(198)(199)(200)(201)(202)(203) and iron (66,148,166,167,171,176,(179)(180)(181)(193)(194)(195)201,(204)(205)(206)(207) have been widely investigated recently. Abdelouahab et al (193) considered the effects of these promoters on the structure of catalysts prepared with organic solvents.…”
Section: In the Activementioning
confidence: 99%
“…Our group has been investigated the effect of the different calcinations duration of nbutane/air pretreatment on the vanadium phosphate catalysts synthesized via organic method 4,5 . In this paper, we would like to study the effect of different calcination duration on the vanadium phosphate catalysts prepared via VPO 6,7 and VPD 6,8,9 method . The precursors were calcined in an inert environment to produce catalysts which mainly consist of (VO) 2 P 2 O 7 phase.…”
Section: Introductionmentioning
confidence: 99%